2013
DOI: 10.1128/ec.00040-13
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Sexual Cycle in Aspergillus lentulus, a Close Relative of A. fumigatus

Abstract: Aspergillus lentulus was described in 2005 as a new species within the A. fumigatus sensu lato complex. It is an opportunistic human pathogen causing invasive aspergillosis with high mortality rates, and it has been isolated from clinical and environmental sources. The species is morphologically nearly identical to A. fumigatus sensu stricto, and this similarity has resulted in their frequent misidentification. Comparative studies show that A. lentulus has some distinguishing growth features and decreased in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 66 publications
4
31
2
2
Order By: Relevance
“…(Table 3). Intraspecific mating was observed between several A. lentulus strains of the opposite mating type, confirming the functional heterothallism of this species (9). Analysis of 8-week-old crosses between CM-5027 and CM-5563, the most fertile A. lentulus isolates, revealed abundant cleistothecia in the junction zones of the two opposite mating type strains.…”
Section: Genetic and Biological Species In Section Fumigatisupporting
confidence: 62%
See 1 more Smart Citation
“…(Table 3). Intraspecific mating was observed between several A. lentulus strains of the opposite mating type, confirming the functional heterothallism of this species (9). Analysis of 8-week-old crosses between CM-5027 and CM-5563, the most fertile A. lentulus isolates, revealed abundant cleistothecia in the junction zones of the two opposite mating type strains.…”
Section: Genetic and Biological Species In Section Fumigatisupporting
confidence: 62%
“…Recently, heterothallic sexual cycles were discovered in A. lentulus (9) and A. felis (10). Although the sexual state of Aspergillus viridinutans has yet to be found, the presence of the MAT1-1 (11) mating type homolog in the type strain NRRL 4365 suggests heterothallic sexuality.…”
mentioning
confidence: 99%
“…A subsequent study, while confirming these aspects of the population genetic structure of A. fumigatus, also found evidence of a genetic barrier to gene flow, suggesting A. fumigatus contained two (or perhaps more) cryptic and morphologically identical species [68]. More recent studies have confirmed the occurrence of a separate sexual species, A. lentulus [71] and have hinted at the existence of further genetic diversity within A. fumigatus sensu stricto.…”
Section: Population Structure Of Azole-resistant Aspergillus Fumigatusmentioning
confidence: 68%
“…Five patients had a The Netherlands Figure 2. Phylogenetic analysis of azole-susceptible and -resistant A. fumigatus isolates from UK, The Netherlands, India and Japan [68,71]. Bootstrap analysis using 100 replicated was performed on WGS SNP data to generate a maximum-likelihood phylogeny, with all branches supported to 68% or higher.…”
Section: Clinical Implications Of Resistancementioning
confidence: 99%
“…Of these, A. udagawae, A. lentulus, and A. pseudofischeri have been reported more frequently (Padhye et al 1994;Alcazar-Fuoli et al 2008;Alhambra et al 2008;Vinh et al 2009b;Gyotoku et al 2012;Zbinden et al 2012) than the other eight species (Lonial et al 1997;Guarro et al 2002;Yaguchi et al 2007;Alcazar-Fuoli et al 2008;Shivaprakash et al 2009;Vinh et al 2009a;Barrs et al 2013;Malejczyk et al 2013;Pelaez et al 2013;Singh et al 2013). A sexual state (Neosartorya) was described in nine of the 12 pathogenic species in the section Fumigati (Samson et al 2007;O'Gorman et al 2009;Swilaiman et al 2013). It could be that the three asexual species, A. fumisynnematus, A. fumigatiaffinis, and A. novofumigatus, require nonconventional growth conditions to undergo the sexual cycle, as was the case with A. fumigatus (O'Gorman et al 2009).…”
Section: A Fumigatus and Other Pathogenic Members Of Section Fumigatimentioning
confidence: 99%